Mustafa Kemal's instructions (an intercepted and decyphered telegram) to Bekir Sami in London, a reassessment of the London conference (21 February-12 March 1921) and its immediate consequences - Kurat, Yuluğ Tekin. (Ankara)
55-93 s.